IMPLEMENTASI METODE SYARH HADIS PADA HADIS-HADIS TENTANG ISLAM, IMAN DAN IHSAN - Siregar, Muhammad Nuh (UIN Sumatera Utara Medan, 2020)
In the general public, there is still debate about the understanding between Islam and faith, whether it is different or the same. Likewise, which one is first in a person, is Islam new faith or faith first then Islam? In answering this question, of course, a comprehensive study from various points of view is necessary. This paper will examine in detail from the point of view of specific Hadith studies. In the Hadith study specifically, this discussion is found in several narrations which are popularly known as the Hadith